Changes in Oncological Surgical Principles Driven by Advances in Preoperative Treatments - Horváth ÖP; Bellyei S; Pozsgai É; Vereczkei A (Dove Medical Press, 2023)
Örs Péter Horváth,1 Szabolcs Bellyei,2 Éva Pozsgai,3,4 András Vereczkei1 1Department of Surgery, University of Pécs Clinical Center, Pécs, 7624, Hungary; 2Department of Oncotherapy, University of Pécs Clinical Center, Pécs, 7624, Hungary; 3Department of Public Health, University of Pécs Medical School, Pécs, 7624, Hungary; 4Department of Primary Health Care, University of Pécs Medical School, Pécs, 7623, HungaryCorrespondence: Örs Péter Horváth, Department of Surgery, University of Pécs Clinical Center, Ifjúság Street 13, Pécs, 7624, Hungary, Tel +3672535806, Email horvath.ors.peter@pte.huAbstract: From a surgical point of view, the development of preoperative oncological treatment has had a profound effect on the surgical treatment trends of cancer as well as on the outcomes of cancer patients. Consequently, these changes have challenged formerly entrenched oncological surgical principles. In our short report, we aimed to summarize the main shifts regarding the surgical principles of cancer treatment due to the development of preoperative oncological therapy in recent years. As a result of successful preoperative treatment, surgeons may perform less radical surgeries, the required free resection margin has been narrowed down to a few millimeters in dimension and preoperative treatment is justified in both definitely resectable tumors and in oligometastatic tumors as well. For prognosis assessment, the post-preoperative oncological treatment stage is now considered decisive, rather than the pretreatment stage as previously thought. Other changes include the introduction of the watch and wait strategy and the reverse order of treatment of the primary tumor and metastasis. Observing the continuously improving outcomes of cancer patients and the developments in oncological treatment modalities, a further expansion of the indication of preoperative treatments is to be expected.Keywords: preoperative oncological therapy, neoadjuvant, downstaging, complete remission, surgical principles